Enhancement of the Ductility Index of Concrete Pavement Using Moderate-Volume of Hybrid Fibers - Sahib Banyhussan, Qais (International Journal of Engineering and Technology, 2018)
The concrete used in highway structures such as pavements, bridge approach slabs or bridge decks are deteriorated much faster rate than other concrete structures due to environmental and traffic loads leading to sudden failure and/or more cracking potential. The present paper investigates experimentally the development of ductile concrete mixtures. Twenty-four mixtures with three types of fibers (PVA, Hocked steel fiber and Nylo-mono) were used. River sand as a fine aggregate and coarse aggregate with a maximum aggregate size of (9.5 mm) were adopted. Fly ash was used as a replacement of Portland cement with three ratios. Compressive and flexural strengths tests were achieved at different curing ages (7, 28 and 90 days) to determine the stress and ductility indexes. The results show thatÂ due to more fly ash content there is an increase in the stress index and decrease in the ductility index for mixtures containing 1% steel and 1% PVA fibers by volume. In addition, the results demonstrated that using of Nylo-mono enhances the ductility index better than PVA. Finally, the use of 2% by volume hybrid fiber (PVA0.5+Steel.0%+Nylo-mono 0.5) achieved a ductile concrete mixture that has a ductility index nine times higher than that of plain concrete. Â Â